2017
DOI: 10.3324/haematol.2017.182642
|View full text |Cite
|
Sign up to set email alerts
|

Unsatisfactory efficacy in randomized study of reduced-dose CPX-351 for medically less fit adults with newly diagnosed acute myeloid leukemia or other high-grade myeloid neoplasm

Abstract: . Unsatisfactory efficacy in randomized study of reduced-dose CPX-351 for medically less fit adults with newly diagnosed acute myeloid leukemia or other high-grade myeloid neoplasm. Haematologica. 2017; 102:xxx doi:10.3324/haematol.2017.182642 Publisher's Disclaimer. E-publishing ahead of print is increasingly important for the rapid dissemination of science. Haematologica is, therefore, E-publishing PDF files of an early version of manuscripts that have completed a regular peer review and have been accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…We performed a trial with reduced doses of CPX-351 for patients with a high TRM score (≥13.1, which corresponds roughly to a 13% chance of dying in the first 28 days after induction), which showed minimal efficacy without adequate improvement in toxicity. [22] An ongoing study at our center randomizes patients with a similarly high TRM score to full-dose G-CLAM or reduced-dose G-CLAM (NCT03012672). Additionally, a recent provocative study from MD Anderson Cancer Center specifically enrolled patients who did not meet eligibility criteria for other trials, demonstrating that treatment of such "ineligible" patients was feasible.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a trial with reduced doses of CPX-351 for patients with a high TRM score (≥13.1, which corresponds roughly to a 13% chance of dying in the first 28 days after induction), which showed minimal efficacy without adequate improvement in toxicity. [22] An ongoing study at our center randomizes patients with a similarly high TRM score to full-dose G-CLAM or reduced-dose G-CLAM (NCT03012672). Additionally, a recent provocative study from MD Anderson Cancer Center specifically enrolled patients who did not meet eligibility criteria for other trials, demonstrating that treatment of such "ineligible" patients was feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Walter and colleagues evaluated the use of reduced doses of CPX-351 (32 or 64 units/m 2 ) in patients with comorbidities and found that a reduction of treatment-related mortality could not be achieved while maintaining the CR rate. 22 For patients who achieve CR, the administration of additional chemotherapy is generally deemed necessary, although no standard postremission therapy has been established thus far. The ALFA-9803 trial compared the administration of one course of intensive consolidation (daunorubicin 45 mg/m 2 /day or idarubicin 9 mg/m 2 for 4 days in combination with cytarabine 200 mg/m 2 IV for 7 days) with repeated cycles of less-intensive consolidation courses (either 45 mg/m 2 daunorubicin or 9 mg/m 2 idarubicin for 1 day in combination with 60 mg/m 2 /12 h cytarabine for 5 days), in elderly patients (age > 50 years) in first CR.…”
Section: Intensive Chemotherapymentioning
confidence: 99%
“…Walter and colleagues evaluated the use of reduced doses of CPX-351 (32 or 64 units/m 2 ) in patients with comorbidities and found that a reduction of treatment-related mortality could not be achieved while maintaining the CR rate. 22…”
Section: Introductionmentioning
confidence: 99%
“…Although CPX‐351 has primarily been studied as intensive chemotherapy, a phase 2 study evaluated lower‐intensity doses of CPX‐351 in adults with newly diagnosed AML who were considered less fit and had a composite treatment‐related mortality score of >13.1 (corresponding to a >13.1% probability of death within 28 days of receiving intensive chemotherapy) 64 . Among patients who received CPX‐351 32 units/m 2 /dose (n = 38) and 64 units/m 2 /dose (n = 10), respectively, the CR + CRi rates were 29% and 20%, 12‐month OS rates were 17% and 20%, and early mortality rates within 28 days were 29% and 40% 64 . An ongoing clinical trial is also evaluating lower‐intensity CPX‐351 plus venetoclax in adults considered unfit for intensive therapy (http://clinicaltrials.gov Identifier NCT04038437).…”
Section: Therapeutic Approaches In Older And/or Unfit Patient Populatmentioning
confidence: 99%